Greenhouse gases utilization: A review - Jeffry L.; Ong M.Y.; Nomanbhay S.; Mofijur M.; Mubashir M.; Show P.L. (Elsevier Ltd, 2023)
Catalysts; Electrolytic reduction; Energy policy; Fossil fuels; Global warming; Greenhouse effect; Greenhouse gases; Methane; Advanced catalyst systems; Carbon capture and utilization; CH$-4$; Climate change mitigation; Electrochemical reductions; Gas utilization; Greenhouses gas; Methane utilization; Photocatalytic reduction; Plasma technology; Carbon dioxide